Use it too much and lose everything? The effects of hours of work on health - Shinya Kajitani; Colin McKenzie; Kei Sakata (Elsevier, 2022)
In this paper, we extend the 'use it or lose it' hypothesis to analyse whether the negative effects of working hours eventually dominate the positive effects of work as the hours of work increase. Using panel data from the HILDA survey, we estimate the optimal hours of work for the health status of middle age and elderly workers. We deal with the potential endogeneity of working hours by using the instrumental variable estimation technique with instruments based on the age for pension eligibility. For males working relatively moderate hours (up to around 24-27 h a week), an increase in working hours has a positive impact on their health outcomes, but thereafter an increase in working hours has a negative impact on health outcomes. When weekly working hours exceed 50 h, an individual's health status is worse off than when he is not working at all.